Free Trade Agreement between Morocco and the United States of America (Track and bets) - Chaouki, Hind (Eximia, 2023)
After the end of World War II, international trade relations developed significantly in the volume of exchanges, besides in their quality and in the status of the parties involved. The resources in question have also varied from raw to manufactured and semi-manufactured materials, although the trade in facilities has become an important part of international exchanges. (Dr. Al-Hassan Bouqantar, 2022). Shared relations are no longer limited to traditional trading countries, but have exceeded them to developing countries, as this phase has been categorized by an increase in the number of bilateral and multilateral agreements in the trade field, not to mention the establishment of free trade zones, customs contacts and regional and global organizations. Facing the rapid and rapid liberalization of trade at the global level, economic sincerity is no longer a choice for Morocco, but as a realistic given that must accept a strategy which enables it to control it, to take advantage of its positives and avoid its disadvantages. (Husseini, 2001). Moroccan-American relations date back to the early years of the U.S. War of Independence. Morocco was the first country outside Europe to identify the emerging republic.the establishment of political and trade links between countries came first and foremost as a result of the desire of the efforts of Sultan Muhammad bin Abdullah (1757-1790), who followed a policy of economic and trade openness.